Adjusting hydrogen bond by Lever Principle to achieve high performance starch-based biodegradable films with low migration quantity. (15th December 2022) - Li, Xiangyu; Gao, Bingbing; Zhang, Shuidong
Abstract: To adopt carbohydrate polymers as biodegradable plastic is a promising strategy to eliminate the pollution evoked by oil-based plastics. Thermoplastic starch (TPS) with different glycerol and tartaric acid (TA) contents were prepared by twin-screw extrusion, then extruded with poly (butyleneadipate-co-terephthalate) (PBAT) to obtain PBAT/TPS. A "Lever Principle" was adopted for adjusting the hydrogen bond strength of TPS by varying TA and glycerol contents which influenced the blocking force, mechanical properties and migration quantity of PBAT/TPS (PT) films manufactured by film blowing. Noteworthy, as the glycerol content decreased from 27.5 to 15 %, with 25 times "Lever Principle" for increasing TA content, the migration weight and blocking force decreased from 5.8 % and 58.4 × 10 −4  N/mm for HPT0.5–27.5 to 1.7 % and 29.1 × 10 −4  N/mm for HPT0.5–15 with 15.2 MPa tensile strength. This study adopted "Lever Principle" to adjust hydrogen bond strength, which could realize the good performance with low migration quantity for biodegradable PT films. Graphical abstract: Unlabelled Image